Finance and corporate governance in sporting sector / Bernard Mnzava - Mnzava, Bernard (Faculty of Business Management, 2013)
This article reviews the literature of finance conducted in the sporting sector with focus on corporate governance. The objective of this survey is to sorts the literature along three dimensions that reflect key research issues in the field of corporate governance.The methodology used is to read and summarize the findings of several papers in each group on these dimensions. First, the article reviews the perception of managerial succession and sporting performance. Second, the survey covers research on managerial efficiency and sporting performance. Finally, my article articulates the interrelationships between sporting performance and financial performance. On this agenda, the findings demonstrate that sporting performance influences financial performance and vice-versa. This survey is original as it helps to highlight areas where finance research in the sporting sector has stalled, areas it has ignored, as well as providing direction for rebootingthe field by outlining questions for future research and theory building.